The Effect of Work Stress, Internal Communication, and Work Motivation on Employee Performance at PT. PLN (Persero) UIP SUMBAGSEL - Dina Puspitasari; Agustina Marzuki; Irayani Irayani; Sari Sakarina (The Eastasouth Journal of Social Science and Humanities, 2026)
At PT. PLN (Persero) UIP SUMBAGSEL, this study aims to investigate the concurrent and individual effects of work stress, internal communication, and work motivation on employee performance. The study used structured questionnaires to collect primary data using a quantitative technique with a descriptive framework. Using the Slovin algorithm and a random selection technique, 68 participants were chosen from the target population of 210 employees. Following the completion of validity, reliability, and normality investigations using SPSS 27, multiple linear regression analysis, t-tests, F-tests, and coefficient of determination (R²) calculations were carried out. The F-test result (significance value of 0.000, which is less than 0.005) indicates a statistically significant combined effect of work stress, internal communication, and work motivation on employee performance. The partial t-test findings for individual impacts indicate that neither job stress (significance value of 0.502, over 0.005) nor internal communication (significance value of 0.243, also higher than 0.005) significantly affect employee performance. Work motivation does, however, demonstrate a significant positive influence on employee performance with a significance value of 0.001, which is less than the 0.005 limit.